Cardiac murmur in a neonate: how significant is it? - Pathak, Gargi H.; Chauhan, Anuya V.; Nayak, Kesha (International Journal of Contemporary Pediatrics, 2020)
Background: There is a popular belief that cardiac murmurs are common in neonate and most are innocent or physiological. However, a cardiac murmur may be the first sign of a serious structural cardiac disease in neonate. Objective of study was conducted to determine the clinical significance of cardiac murmur as a sole clinical sign in neonate. Methods: 100 neonates having cardiac murmur were selected from neonatal intensive care unit of department of pediatrics BJMC Ahmedabad from June to November 2019. Murmurs were clinically classified as innocent or significant murmur. Echocardiography was done at UN Mehta institute of cardiology for confirmation of the diagnosis and then patients were reclassified as innocent murmur and structural heart defect. structural heart defects were further subdivided into physiological variant or significant heart defect. Results: Amongst 100 neonates studied, sixty two percent cases with murmur were found to have structural heart defect and 38% had innocent murmur. Among the cases with structural heart defect. 65.3% were found to have significant heart defect and 34.7% were physiological variant. Clinical suspicion was able to differentiate innocent murmur or structural heart defect (p<0.05) as well as physiological variant versus significant heart defect (p<0.05). Conclusions: Confident diagnosis of heart disease in the newborn period on clinical examination is probably possible by pediatricians or neonatologists. However, for confirmation of diagnosis, early echocardiographic evaluation is necessary.